Evaluation of various water quality indices for indexing river water - Choo, Chee Yuan (University Malaysia Sarawak, UNIMAS, 2014)
Water resources are of critical importance to both natural ecosystem and human development. The quality of water in any ecosystem provides significant information about the available resources for supporting life in that ecosystem. A good water quality is important for a healthy river and ecosystem. In order to determine the status of the river water, various water quality parameters are measured to determine whether it is safe for any purpose. The water quality parameters can be divided into physical, chemical and biological. Most of the physiochemical and microbiological parameters were measured and classified based on the National Water Quality Standard (NWQS) and Water Quality Index (WQI) to evaluate the status of river water quality. In this study, three water quality monitoring approaches was used to evaluate the Waterfront and Satok Bridge river water which are Water Quality Index (WQI), average National Water Quality Standards (NWQS) and Partial Least Square Water Quality Index (PLS-WQI). PLS-WQI is designated based on Partial Least Square Regression that can consider expand or restrict parameters simultaneously instead of the conventional univariate manner according to NWQS. Besides, PLS-WQI is a set of computationally generated training sets that can be used to predict the water quality of unknown samples. In this study, the river water quality was categorized as Class II-Class III under WQI which is moderate to good water quality with index ranged from 75 to 86. The PLS-WQI was more sensitive than average NWQS because it took into account the entire value for each parameter and not only interpreted the class which each parameter value fell on it. PLS-WQI is a method that can consider multiple parameters simultaneously. Therefore, when the turbidity parameter was added, it showed that PLS-WQI with 7 parameters was more sensitive than the PLS-WQI with 6 parameters because PLS-WQI took the absolute value of the parameter into account to determine the classes of the water quality. Therefore, PLS-WQI should be encourage to be used in the evaluation of river water quality status in Malaysia to meet with the specific problems.